Transformative translanguaging espacios Latinx students and their teachers : rompiendo fronteras sin miedo - Sánchez, Maite T. 1972-; García, Ofelia 1949- (Multilingual Matters, 2022)
"This book shows the transformative power of placing translanguaging at the center of teaching and learning. It shows how the centering of racialized Latinx bilingual students, including their knowledge systems and cultural and linguistic practices, transforms the monolingual-white supremacy ideology of many educational spaces"--
Keywords: Hispanos; Zweisprachigkeit; Englischunterricht; USA; Hispanic Americans / Education; Hispanic Americans / Languages; Translanguaging (Linguistics); Education, Bilingual / United States; Language and education / United States; Education, Bilingual; Language and education; United States; Aufsatzsammlung